The Effect Of Setting Time And Hauling Purse Seine On Catches At KM Bangkit Lautan Jaya5 - Wulandari, Ully; Sutono, Dian; Prakoso, Danang Ali (Barakuda 45: Jurnal Ilmu Perikanan dan Kelautan, 2023)
The purpose of the study was to determine the effect of the length of time setting and hauling purse seine on the caught fish. The object of study is KM. Rising Lautan Jaya 5. The study was conducted from 1 to 4 June 2022 at the PPS Nizam Zachman Ocean Fishing Port in Jakarta. This study adopted a simple linear regression analysis to determine the correlation between setting time and hauling purse seine to caught fish. The results of the analysis in this study showed a relationship between the length of time and hauling of the catch in purse seine capture operations. The results of the normal distributed data test were 0.079 and 0.200, and there was a linear relationship of 0.783 and 0.880 so that the regression test results of 0.004 and 0.001 were found. Thus the results of the regression test can be interpreted to mean that there is an influence between the length of time setting and hauling on the catch